Bacal's obsession with a palace of his own - Da Sliva, A. A. (Journal for semitics, 1990)
Bacal's obsession with a palace of his own. This article endeavours to find answers to three questions about the so-called ""building""-motif in the Bacal cycle (texts KTU 1.1-1.4). To the first question (Why didn't Bacal have a house of his own?) the answer is given that Bacal, not having a house, reflects the early stage of his integration into Ugarit's pantheon of which he originally wasn't a part. The answer to the second question (Why was Bacal so anxious to have a house of his own?) is sought in the thesis that it reflected the Bacal-worshippers' wish to gain dominance in Ugarit's cult. The answer to the third question (Why did Bacal have to get El's permission to build a house?) is that El, although he was eventually displaced by Bacal as king of Up's gods, was not completely abandoned. He was still held in high esteem and still seen as the sole commander on a number of matters under his jurisdiction.